2005
DOI: 10.1158/0008-5472.can-04-2991
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Antigen-Presenting Cells Transduced with Telomerase Efficiently Expand Epitope-Specific, Human Leukocyte Antigen–Restricted Cytotoxic T Cells

Abstract: Human telomerase reverse transcriptase (hTERT) is overexpressed in most human tumors, making it a potential target for cancer immunotherapy. hTERT-derived CTL epitopes have been identified previously, including p865 (RLVDDFLLV) and p540 (ILAKFLHWL), which are restricted by the human leukocyte antigen (HLA) class I A*0201 allele. However, it remains a major challenge to efficiently and consistently expand hTERT-specific CTLs from donor peripheral blood T lymphocytes. To bypass the need for generating convention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 55 publications
3
46
0
Order By: Relevance
“…However, the self-limitation of insect cells at 37 o C (the viable temperature for D. melanogaster cells is 27 o C) could lead to massive release of D. melanogaster antigens and limit the duration of the contact between the T cell and the aAPC (16,17). Mouse fibroblasts yielded on average 30 × 10 6 specific CTLs, however much higher T-cell doses may be required in the clinic (18)(19)(20). The bead-based systems also have some drawbacks, including high cost of the beads, the labor-intensive process of removing the beads from the culture before infusion, and the inability of these beads to expand CD8 + T cells (21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…However, the self-limitation of insect cells at 37 o C (the viable temperature for D. melanogaster cells is 27 o C) could lead to massive release of D. melanogaster antigens and limit the duration of the contact between the T cell and the aAPC (16,17). Mouse fibroblasts yielded on average 30 × 10 6 specific CTLs, however much higher T-cell doses may be required in the clinic (18)(19)(20). The bead-based systems also have some drawbacks, including high cost of the beads, the labor-intensive process of removing the beads from the culture before infusion, and the inability of these beads to expand CD8 + T cells (21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…Tetramer-positive T cells specific for the hTERT 540 -548 peptide have been detected in the peripheral blood of cancer patients (44), and this putative epitope has become the main focus for T-cell therapies. Several groups have grown polyclonal T-cell lines which have been reported to kill HLA A2 + , telomerase + tumor cell lines and primary tumors (16,24,25). However, two other groups have reported that T-cell clones to this epitope do not kill tumor cells (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Three groups (16,24,25) reported that polyclonal CTL lines specific for this pMHC can lyse tumor cells exhibiting telomerase activity. However, two subsequent studies using monoclonal CTL populations could not reproduce these observations (26,27).…”
Section: Introductionmentioning
confidence: 99%
“…Murine NIH/3T3 fibroblasts were used for generation of HHD-restricted APCs because they were shown to be capable of processing and presenting the same viral and tumor HLA-A*0201 restricted epitopes, which were immunogenic in humans. 28,29 Both the TEL-AML1 fusion region and Melan-A/MART-1 were cloned into the retroviral vector pMP71 16 in identical fashion, as a single ORF with EGFP and Ub moiety ( Figure 4A), according to the Ub/protein/ reference (UPR) technique. 18 The tripartite fusion comprising the test antigen (TEL-AML1), or the control tumor antigen To show that the generated NIH-HHD cells can efficiently present peptide antigens to CD8 ϩ T cells, we loaded the cells with the nonamer peptides used for the immunization (TEL-AML1-9V or Melan-A/MART-1) and cocultured them with the pooled spleen and LN cells from the immunized mice.…”
Section: The Tel-aml1 Peptide Is Not Endogenously Processedmentioning
confidence: 99%